Luminosity Evolution of the Hot Gas in Normal Galaxies from the Near Universe to z = 0.5 - Dong-Woo Kim; Giuseppina Fabbiano (The Astrophysical Journal)
We explore the evolution of the ∼10 ^7 K hot gas in normal galaxies out to redshift = 0.5 (lookback time = 5 Gyr), using X-ray luminosity functions (XLFs) built from a sample of 575 normal galaxies with z < 0.6 detected in five high-galactic-latitude Chandra wide-field surveys. After estimating the emission due to the hot gas component (reducing the sample to ∼400 galaxies), we compared the XLF in three redshift bins ( z = 0.1, 0.3, and 0.5), finding increases in the number of galaxies per unit comoving volume from z = 0.1 to 0.3 and then from z = 0.3 to 0.5. These XLF changes suggest a significant (∼5 σ ) X-ray luminosity evolution of the hot gas, with L _X,GAS decreasing by a factor of 6–10 in the last 5 Gyr (from z = 0.5 to 0.1). The relative abundance of L _X,GAS ∼ 10 ^41 erg s ^−1 galaxies at higher z suggests that high -z , moderate -L _X,GAS galaxies may be the optimal target to solve the missing baryon problem. In early-type galaxies, this observational trend is qualitatively consistent with (but larger than) the expected time-dependent mass-loss rate in cooling flow models without active galactic nucleus feedback. In late-type galaxies, the observational trend is also qualitatively consistent with (but larger than) the effect of the z -dependent star formation rate.